Metal halide perovskites for resistive switching memory devices and artificial synapses. Issue 25 (12th June 2019) - Li, Bixin; Hui, Wei; Ran, Xueqin; Xia, Yingdong; Xia, Fei; Chao, Lingfeng; Chen, Yonghua; Huang, Wei
Abstract : This article highlights recent developments of emerging metal halide perovskite based resistive switching memory devices and artificial synapses. Abstract : Rapid progress of digital communications in the Big Data and Internet of things has stimulated the exploration of next-generation data storage devices. Among various candidates, resistive switching (RS) memory devices and artificial synapses are in the spotlight due to their low power consumption, downscaling potential, and fast operation speed. The exceptional electronic and mechanical characteristics of metal halide perovskites (MHPs) have greatly promoted their application in nonvolatile high density, low-cost, and flexible memory devices. Here, we distill the current state-of-the-art and highlight recent advances of MHP based RS memory devices and artificial synapses. The general structure and characteristics of RS memory devices are first introduced. Afterwards we discuss the excellent memory behaviors accompanied by detailed working mechanisms. Finally, the current challenges and future development prospects are also discussed. This review article is expected to pave the way in the rational design of MHP based memory devices and artificial synapses with unprecedented performance improvement.